Exposure to the Gram-Negative Bacteria Pseudomonas aeruginosa Influences the Lung Dendritic Cell Population Signature by Interfering With CD103 Expression - Brassard, Julyanne; Roy, Joanny; Lemay, Anne-Marie; Beaulieu, Marie-Josée; Bernatchez, Emilie; Veillette, Marc; Duchaine, Caroline; Blanchet, Marie-Renée (Frontiers in Cellular and Infection Microbiology, 2021)
Lung dendritic cells (DCs) are divided into two major populations, which include CD103+XCR1+ cDC1s and CD11b+Sirpα+ cDC2s. The maintenance of their relative proportions is dynamic and lung inflammation, such as caused by exposure to lipopolysaccharide (LPS), a component of the outer membrane of Gram negative bacteria, can have a significant impact on the local cDC signature. Alterations in the lung cDC signature could modify the capacity of the immune system to respond to various pathogens. We consequently aimed to assess the impact of the Gram negative bacteria Pseudomonas aeruginosa on lung cDC1 and cDC2 populations, and to identify the mechanisms leading to alterations in cDC populations. We observed that exposure to P. aeruginosa decreased the proportions of CD103+XCR1+ cDC1s, while increasing that of CD11b+ DCs. We identified two potential mechanisms involved in this modulation of lung cDC populations. First, we observed an increase in bone marrow pre-DC IRF4 expression suggesting a higher propensity of pre-DCs to differentiate towards the cDC2 lineage. This observation was combined to a reduced capacity of lung XCR1+ DC1s to express CD103. In vitro, we demonstrated that GM-CSF-induced CD103 expression on cDCs depends on GM-CSF receptor internalization and RUNX1 activity. Furthermore, we observed that cDCs stimulation with LPS or P. aeruginosa reduced the proportions of intracellular GM-CSF receptor and decreased RUNX1 mRNA expression. Altogether, these results suggest that alterations in GM CSF receptor intracellular localisation and RUNX1 signaling could be involved in the reduced CD103 expression on cDC1 in response to P. aeruginosa. To verify whether the capacity of cDCs to express CD103 following P. aeruginosa exposure impacts the immune response, WT and Cd103 /- mice were exposed to P. aeruginosa. Lack of CD103 expression led to an increase in the number of neutrophils in the airways, suggesting that lack of CD103 expression on cDC1s could favor the innate immune response to this bacterium.